Emergence: Examining Gender in Music through Contemporary Opera - FELICITY WILCOX (Sound Stage Screen)
What does it mean to be part of a music industry that, for centuries, has ignored your perspective, undermined your talent and confidence, objectified your body, and systematically erased composers like you from the canon? An acclaimed Australian composer here shares aspects of her current research project on contemporary opera, funded through the Australian Research Council. Incorporating research undertaken with leading practitioners of contemporary opera and data from the author's recent report, Women and Minority Genders in Music (Wilcox and Shannon 2023), this paper interweaves first-source interview data, auto-ethnographic reflection, qualitative and quantitative analysis, and a selective overview of contemporary global practice to examine the structural inequity at opera’s core, and new disruptive practice that challenges the status quo. The author ties together theoretical discourse on intersectional feminism (Lorde 1984), feminist listening (Lehmann and Palme 2022), and acoustic ecology (Westerkamp 2002) to outline a compositional approach that engages experimentally with sound through guided improvisations on music and text, extended techniques, explorations of embodiment, "deep listening" (Oliveros 2005), and consultative conceptual development that respects and welcomes difference. Extending this to a broader context, she suggests frameworks for more inclusive practice and audience engagement in opera.